Brentidae of Peru (Coleoptera: Curculionoidea) - Mantilleri, Antoine; Bartolozzi, Luca; Sforzi, Alessandra (Zootaxa, 2017)
Eighty-four species of Brentidae (not including Apioninae) are listed from Peru, 13 presently only known from this country. Stereodermus platycornis Mantilleri, sp. nov. and Teramocerus spathulifer Mantilleri, sp. nov., are described from Tambopata Province. A micropterous species, Stereodermus micropterus Mantilleri, sp. nov., is described from Alto Madre de Dios River. Stereodermus barbirostris Sharp, 1895, S. breviceps Sharp, 1895, S. nigriceps Sharp, 1895, Pertusius errabundus (Kleine, 1927), Rugosacratus punctirostris (Boheman, 1840), Teramocerus appendiculatus (Soares & Scivittaro, 1972), T. eletus Kleine, 1927, and T. suturalis (Lund, 1800), are newly recorded from Peru.